Mechanism of NF-κB signaling in BMP-2-induced dental stem cell odontogeneic differentiation on human amniotic membrane scaffold - Chandra, Hamshawagini (2018)
Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signalling pathway is involved in the tooth organogenesis and eruption process. With the elimination of NF-κB pathway could lead to a developmental detention of teeth. However, the influence of NF-κB signalling in tooth development as well as odontogenesis study remains unclear. Hence, this study was conducted to investigate the mechanism of NF-κB signalling in the differentiation of stem cells derived from human exfoliated deciduous teeth (SHED) into odontoblast-like cells. Analysis of NF- κB signalling was divided into two phases. The first phase was aimed to identify the optimal concentration of carbobenzoxy-L-leucyl-L-leucyl-L-leucinal (MG 132) and ammonium pyrrolidinedithiocarbamate (PDTC). SHED were cultured on human amniotic membrane (HAM) and treated with bone morphogenetic protein-2 (BMP-2). Experimental groups were assigned into four as follows: SHED only (S), SHED cultured on HAM (SA), SHED cultured on HAM treated with BMP-2 (SAB), SHED cultured on HAM treated with BMP-2 and MG 132 inhibitor (SABM), and SHED cultured on HAM treated with BMP-2 and PDTC inhibitor (SABP). Based on the NF- κB protein expression, 0.1 μM and 25 μM of MG 132 and PDTC, respectively, were selected as an optimal concentration to inhibit NF-κB signalling. Thereafter, the second phase of the study was aimed to investigate the expression of stem cell, odontogeneic, and NF-κB gene markers. Following treatment, SHED were harvested on day 1, 7, 10 and 14. Further analyses were carried out using real time reverse transcription polymerase chain reaction (real time RT-PCR). Results showed that the expression levels of stem cell gene markers, Nestin, Nanog, and CD29 were fluctuated in all groups. Besides that, the results of the present study showed that SHED treated with BMP-2 and cultured on HAM showed an increased at day 1 and 7 in the expression of odontogeneic markers, namely, dentine sialophosphoprotein (DSPP) (1.80 ± 0.06; 2.41 ± 0.01) and alkaline phosphatase (ALP) (2.01 ± 0.01; 4.60 ± 0.21). This indicated that SHED had successfully differentiated into odontoblast-like-cells. Meanwhile, treatment with PDTC or MG 132 showed a decreased expression of ALP and DSPP indicating that NF-κB signalling is directly involves in SHED differentiation and mineralisation. On the other hand, the interaction of HAM and BMP-2 with SHED increased the Aquaporin 5 (AQP5) expression at day 7 and 10 (1.15 ± 0.01; 2.43 ± 0.24) and Interleukin-8 (IL-8) expression at day 14 (0.88 ± 0.36). While, the treatment with inhibitors decreased the expressions of both genes especially at day 14 for AQP5 and for IL-8 was throughout the experiment. As for Interleukin 1 beta (IL-1β), HAM induced its expression while, the addition of BMP-2 decreased its expression. Addition of the inhibitors also down-regulated its expression. Besides, Tumour necrosis factor (TNF-α) expression was down-regulated in all the groups when BMP-2 was added. A similar pattern of Receptor activator of nuclear factor kappa-Β ligand (RANKL) expression were demonstrated for all the treatment groups suggesting that RANKL was minimally affected by HAM and BMP-2. Results also demonstrated that HAM and BMP-2 increased Osteoprotegerin (OPG) at day 1(1.96 ± 0.05). However, PDTC and MG 132 reduced the expression of OPG after day 7. All statistical analyses were performed at the significance level of p<0.05. In conclusion, based on the gene expression analysis, this study suggested that inhibition of NF-κB directly involves in odontogeneic differentiation of SHED when cultured on HAM with the treatment of BMP-2.